2017
DOI: 10.1016/j.dental.2017.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility and bond degradation of poly-acrylic acid coated copper iodide-adhesives

Abstract: Objective. To investigate the effect of poly-acrylic acid (PAA) copper iodide (CuI) adhesives onbond degradation, tensile strength, and biocompatibility. Methods. PAA-CuI particles were incorporated into Optibond XTR, Optibond Solo and XP Bondin 0.1 and 0.5 mg/ml. Clearfil SE Protect, an MDPB-containing adhesive, was used as control.The adhesives were applied to human dentin, polymerized and restored with compositein 2 mm-increments. Resin–tensilebond strength after 24 h, 6 months and 1 year. Hourglass speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 45 publications
4
20
0
Order By: Relevance
“…One important finding of our screening study is that Self-Etch and Etch-and-Rinse adhesives showed no statistically significant difference in the observed cytotoxic effects in terms of the qualitative evaluation and the reactivity index. This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…One important finding of our screening study is that Self-Etch and Etch-and-Rinse adhesives showed no statistically significant difference in the observed cytotoxic effects in terms of the qualitative evaluation and the reactivity index. This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28].…”
Section: Discussionsupporting
confidence: 93%
“…This is in accordance with other studies [14][15][16][17][18][19]. Self-etch dentin adhesives showed more cytotoxicity regarding the quantitative evaluation, which is also in line with previous studies [14,24,[26][27][28]. Contradictory, other studies found that Etch-and-Rinse adhesives were more cytotoxic [11,17,[20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The authors suggested that this was due to the potentially esterase-inhibiting effect of the particles and the release of copper, though the inhibition was not confirmed. Renne et al also investigated similar polyacrylic acid-coated copper iodide particles, and corroborated previous results confirming antimicrobial efficacy [86]. They also demonstrated a strong ability of the material to inhibit collagen degradation in a simulated body fluid, but did not determine a source of this effect.…”
Section: Current Work To Reduce Biodegradation and Secondary Cariessupporting
confidence: 61%